First record of the microleafhopper genera Mjolnirus and Shumka from China (Cicadellidae: Typhlocybinae: Empoascini), with description of two new species - Wang, Ran; Dietrich, Christopher H.; Zhang, Yalin; Cao, Yanghui (Zootaxa, 2026)
Two genera, Mjolnirus Wang, Xu & Qin, 2021 and Shumka Dworakowska, 1997, are newly recorded from China based on Mjolnirus shenzhenensis sp. nov., Shumka bihamatus sp. nov. and one newly recorded species S. wareeae Dworakowska, 1997 from China (Yunnan and Guangdong). Descriptions, illustrations and keys to males of the known species of these genera are given.